THE EFFECTS OF WATCHING ENGLISH-SUBTITLED VIDEOS ON EFL STUDENTS’ VOCABULARY LEARNING - Rizky Purwa Lestari; Rolisda Yosintha (ELTR Journal, 2022)
This paper studies how watching English-subtitled videos affect EFL (English as a Foreign Language) students’ vocabulary learning. 20 English major students watched an English video about a classic ghost tale twice. The control group (n = 10) watched the unsubtitled video, while the experimental group (n = 10) watched the subtitled video. After watching it, they did the test of vocabulary and the test of understanding. A descriptive-qualitative method was utilized in this paper. It reveals that watching a video with its English subtitle affects the vocabulary learning; the experimental group achieved a higher score in both tests than the control group. However, the experimental group’s mean score was only slightly, not significantly, high. Pedagogical implications are found to utilize English-subtitled videos for better vocabulary learning.